2017
DOI: 10.5614/ejgta.2017.5.2.13
|View full text |Cite
|
Sign up to set email alerts
|

On H-irregularity strengths of G-amalgamation of graphs

Abstract: A simple graph G =

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The precise value of the total H-irregularity strength of G-amalgamation of graphs is given in [8] and it proves that the lower bound in Theorem 1.1 is tight.…”
Section: Introductionmentioning
confidence: 86%
“…The precise value of the total H-irregularity strength of G-amalgamation of graphs is given in [8] and it proves that the lower bound in Theorem 1.1 is tight.…”
Section: Introductionmentioning
confidence: 86%
“…Ashraf F. et al [3] found the total P m -irregularity strength of P n with m, n both integer, 2 ≤ m ≤ n, the total C m -irregularity strength of ladder graph L n with n ≥ 3 and m = 4 or m = 6, and the total C 3 -irregularity strength of fan graph F n . Ashraf F. et al [4] determined the exact value of total H-irregularity strengths of G-amalgamation of graphs. Agustin et al [5] found the total H-irregularity strength of shackle and vertex amalgamation of G, namely ths(Shack(H, v, n)), ths(c(Shack(H, v, n))), ths(Amal(H, v, n)) and ths(c(Amal(H, v, n))).…”
Section: Introductionmentioning
confidence: 99%